SMART WEIGHING FOR WASTE MANAGEMENT SYSTEM USING INTEGRATION INTERNET OF THINGS AND ARTIFICIAL INTELLIGENCE TO ASSIST CIRCULAR ECONOMICS - Siti Sendari; Norrima binti Mokthar; Bimastyaji Surya Ramadan; Bakhrul Mukhid Fadilah Ramadani; Fadila Claudia Pramesti; Qurrotul A'ini; Danang Arengga Wibowo; Putra Wisnu Agung Sucipto; Yuni Rahmawati; Fauzy Satrio Wibowo (Universitas Trisakti, 2025)
Aims: This study was aimed to Supit Urang Landfill in Malang, East Java, Indonesia, urgently needs a smart waste management system because it is strategically important as a large landfill with a monthly operating capacity of 4.560 trucks. Landfill management is very challenging due to some cases, such as overcapacity, inefficient waste sorting, and environmental risks. Methodology and results: The research introduced an integration of Internet of Things (IoT) and Artificial Intelligence (AI) into the waste management system to support the principles of a circular economy. IoT was applied for real time monitoring of waste conditions, while AI was utilized for big data analytics, enabling predictions, decision-making support, and policy recommendations. The results demonstrated that the proposed system improves efficiency and cost-effectiveness by reducing the amount of waste disposed of in the landfill and optimizing the waste sorting and recycling process. Conclusion, significance and impact study: The study concludes that the transformation toward a sustainable waste management model is urgently needed and can be achieved through AIoT integration. This innovation supports circular economy practices by enhancing waste reduction, reuse, and recycling. The successful implementation at Supit Urang could serve as a scalable model for other landfills across Indonesia, thereby contributing to national strategies for sustainable waste management. This technological intervention not only improves environmental outcomes by reducing pollution and conserving resources but also fosters economic development through efficient resource utilization and job creation in the recycling and waste processing sectors.